ANALISIS PENGGUNAAN GOOGLE CLASSROOM PADA ASPEK KEAKTIFAN SISWA SMP KELAS VII - Siti Zainab Nur Azizah; Martini Martini; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The purpose of this study was to analyze online learning activities using the LMS Google Classroom during the Covid-19 pandemic on environmental pollution material. The research method used is descriptive qualitative, namely by describing student activities during online learning. The subject of this research were students of SMPN 1 Sidoarjo class 7C and 7E totaling 60 students. The data analysis technique through 3 stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the LMS Google Classroom was vital and helped students to show their learning activeness during online learning. The number of students who are active when learning using Google Classroom is 75,5%. Problems arise during online learning were related as running out of quota, low signal, smartphone errors, attending family events, not being able to access questions that have been assigned and not checking new assignments in Google Classroom. Teachers have made various efforts and provided innovations so that learning using the LMS Google Classroom can foster student activity during online learning and learning materials can be accepted by students to the maximum.